Analisis Sistem Informasi Akuntansi Dalam Penggajian Karyawan Sebagai Usaha Pengendalian Internal pada PT Megaflex Pratama - Dian Maharani; Amin Sadiqin (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
As a company grows, its activities and workforce also increase, making it difficult for management to control the company alone. One of the major obstacles faced by management is managing employee salaries, which can result in inaccuracies in calculating working hours, cutting salaries, calculating employee overtime, and paying salaries due to inaccurate data. The use of an information system can play a crucial role in controlling and preventing such errors. This study employed interviews with relevant parties and observations at PT Megaflex Pratama, as well as descriptive analysis techniques. The findings revealed that there are still ineffective elements of internal control in the payroll of PT Megaflex Pratama employees. These include the personnel department performing double work, submitting and paying salaries directly to employees, as well as entering attendance through an unsupervised fingerprint system without proper authorization.